EDUKASI DAN PELATIHAN RESUSITASI JANTUNG PARU (RJP) PADA REMAJA DI SMAN 5 BANDA ACEH - Nurhidayah, Irfanita; Fikriyanti, Fikriyanti; Aklima, Aklima; Kiftia, Mariatul; Amalia, Riski; Nurhasanah, Nurhasanah; Dewiyanti, Dewiyanti (Universitas Mataram, 2025)
Sudden cardiac arrest is one of the leading causes of death that can actually be prevented if early intervention is carried out quickly and appropriately. However, public awareness and skills—particularly among adolescents—in performing Cardiopulmonary Resuscitation (CPR) remain very low. Therefore, widespread education and training on CPR are essential to increase the chances of survival for victims. This Community Service Program aims to improve adolescents’ ability to provide first aid in cases of cardiac arrest through CPR training and education. Through this program, it is expected that adolescents will gain the knowledge and basic skills necessary to save lives in emergency situations. The target audience of the program was students at SMAN 5 Banda Aceh. The implementation method included education on the signs of cardiac arrest, the importance of CPR, and basic CPR skills training for laypersons, especially teenagers. The activities were conducted interactively through material presentations, hands-on simulation practice, and participant comprehension evaluations to ensure the effectiveness of the training provided. The results of the program showed a significant improvement in understanding the concept of CPR and in basic life-saving skills. Participants were able to recognize the signs of cardiac arrest and perform the CPR steps correctly and in accordance with standards. Additionally, most participants reported feeling more confident in providing first aid in emergency situations after the training. This indicates that direct CPR education and training are highly effective in building community preparedness, especially among adolescents. This community service not only strengthens teenagers' readiness to handle emergency situations but also has the potential to create a sustainable network of first responders. Through this program, it is hoped that the survival rate from sudden cardiac arrest, particularly in school environments, can be increased.